Isolation of a Phytase-Producing Bacterial Strain from Agricultural Soil and its Characterization and Application as an Effective Eco-Friendly Phosphate Solubilizing Bioinoculant. Issue 8 (28th April 2018) - Liu, Lili; Li, Ao; Chen, Juan; Su, Yi; Li, Yuanyuan; Ma, Shengwu
ABSTRACT: In the present study, we isolated from agricultural soils, a Bacillus strain designated SD01N-014, expressing high-level extracellular phytase activity and investigated its potential to be used as a soil phosphate-solubilizing bioinoculant to improve soil phosphorus (P) availability and thus enhance plant growth. Soil inoculation test showed that being as an inoculant, SD01N-014 substantially enhanced soil P nutrition. Pot experiments showed that when applied to soils, SD01N-014 is capable of colonizing maize seedling roots, increasing plant-available P levels in the rhizosphere and promoting seedling growth. High tunnel trials with different vegetable plants demonstrated that SD01N-014 as a soil inoculant greatly promoted plant growth and was positively correlated with inoculum sizes. Together, these results indicate that SD01N-014 holds promising potential as a cheap, viable and eco-friendly alternative to chemical P fertilizers for increasing soil fertility and crop production in sustainable farming.